1983
DOI: 10.1002/j.2161-1920.1983.tb00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling the Older Rural Worker: A Report

Abstract: This project's goals were to sensitize job service counselors to the needs and employment problems of older rural job‐seekers and to develop a model in‐service program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Several studies have demonstrated that vocational rehabilitation programs are effective in assisting unemployed workers' return to the work force (Hurst & Shepard, 1985;Myers, McWilliams, Flanders, & Kohut, 1983;Oliver & Pomicter, 1981;Smith & Hershenson, 1977). Components of an effective vocational rehabilitation program might include the following: (a) assessment of interests and abilities; (b) assistance with job-search skills (e.g., resume writing and interviewing techniques); (c) referrals to career workshops; (d) encouragement of long-term planning; (e) basic literacy instruction;…”
Section: Make Referrals To Vocational Rehabilitation Programsmentioning
confidence: 99%
“…Several studies have demonstrated that vocational rehabilitation programs are effective in assisting unemployed workers' return to the work force (Hurst & Shepard, 1985;Myers, McWilliams, Flanders, & Kohut, 1983;Oliver & Pomicter, 1981;Smith & Hershenson, 1977). Components of an effective vocational rehabilitation program might include the following: (a) assessment of interests and abilities; (b) assistance with job-search skills (e.g., resume writing and interviewing techniques); (c) referrals to career workshops; (d) encouragement of long-term planning; (e) basic literacy instruction;…”
Section: Make Referrals To Vocational Rehabilitation Programsmentioning
confidence: 99%